2016
DOI: 10.1039/c6nr01492e
|View full text |Cite
|
Sign up to set email alerts
|

Optically active red-emitting Cu nanoclusters originating from complexation and redox reaction between copper(ii) andd/l-penicillamine

Abstract: Despite a significant surge in the number of investigations into both optically active Au and Ag nanostructures, there is currently only limited knowledge about optically active Cu nanoclusters (CuNCs) and their potential applications. Here, we have succeeded in preparing a pair of optically active red-emitting CuNCs on the basis of complexation and redox reaction between copper(ii) and penicillamine (Pen) enantiomers, in which Pen serves as both a reducing agent and a stabilizing ligand. Significantly, the Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 35 publications
(30 reference statements)
1
32
0
Order By: Relevance
“…We obtained, in all cases, hybrid CuNCs with intense yellow-green emission (around 535 nm) and high fluorescence QYs, in the region of those obtained by other authors. [42][43][44][45][46][47] As shown in Table 2, no significant changes are observed in the emission band maxima of the nanohybrids with variations in the percentage of thiol present in the polymer or the molecular weight, although these parameters are critical for the obtained QY. The highest fluorescence QY values were obtained for polymers with intermediate thiol content values (6 or 8 mol%) and molecular weights of around 20 kg mol −1 ( Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…We obtained, in all cases, hybrid CuNCs with intense yellow-green emission (around 535 nm) and high fluorescence QYs, in the region of those obtained by other authors. [42][43][44][45][46][47] As shown in Table 2, no significant changes are observed in the emission band maxima of the nanohybrids with variations in the percentage of thiol present in the polymer or the molecular weight, although these parameters are critical for the obtained QY. The highest fluorescence QY values were obtained for polymers with intermediate thiol content values (6 or 8 mol%) and molecular weights of around 20 kg mol −1 ( Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Thus, recently, two overviews of the topic have been published. 40,41 Different biomolecules have been tested as stabilizing ligands for red-emitting CuNCs on the basis of complexation and redox reactions between copper(II) and different biomolecules, such as D-penillamine, 14,20,42 glutathione, 2,35 albumin, 18,43 and cysteine. 44,45 In addition to small ligands, macromolecules have been assayed, giving rise to green-emitting CuNCs with polyvinylpyrrolidone, 46 red-emitting CuNCs with β-galactosidase, 21 blue-emitting CuNCs with lysozyme, 47 and blue and yellow-emitting CuNCs stabilized with trypsin.…”
Section: Resultsmentioning
confidence: 99%
“…From the FTIR spectra of Cu NCs and Ce-Cu NCs aggregates, the broad peaks around 3000-3500 cm −1 represented -NH-and -OH stretching vibration. -COOH stretching vibration at 1525 cm −1 in Cu NCs was absent after adding Ce 3+ and a signal at 1381 cm −1 corresponding to Ce-O bond appeared in Ce-Cu NCs aggregates (Figure 3c), which indicated that Ce 3+ were likely to anchor themselves to -COOH on the capping ligands of Cu NCs through Ce-O bonding [41,42]. Moreover, the stretching vibration of -COOH at 1397 cm −1 in Cu NCs shifted to a higher wavenumber in Ce-Cu NCs aggregates [42].…”
Section: Resultsmentioning
confidence: 99%
“…-COOH stretching vibration at 1525 cm −1 in Cu NCs was absent after adding Ce 3+ and a signal at 1381 cm −1 corresponding to Ce-O bond appeared in Ce-Cu NCs aggregates (Figure 3c), which indicated that Ce 3+ were likely to anchor themselves to -COOH on the capping ligands of Cu NCs through Ce-O bonding [41,42]. Moreover, the stretching vibration of -COOH at 1397 cm −1 in Cu NCs shifted to a higher wavenumber in Ce-Cu NCs aggregates [42]. Since Ce 3+ had a low standard electrode potential of −2.32, it could easily become oxidized and donated electron pairs to form coordinate bonds [43].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, many biological molecules, such as DNA, protein, and amino acid, have been utilized as chiral ligands to design and synthesize chiral Au/Ag nanoclusters, due to the potential applications in photo‐ and electrochemistry, biology, pharmacology, and medicine 3b,10. For example, Yan's group reported a novel CD method for probing l ‐cysteine in biological fluids on the basis of the self‐assembly of chiral nanoparticle from Ag(I) and l ‐cysteine .…”
mentioning
confidence: 99%